Are we ready for Education 4.0 within ASEAN higher education institutions? Thriving for knowledge, industry and humanity in a dynamic higher education ecosystem?. (13th March 2020) - Jamaludin, Rozinah; McKAY, Elspeth; Ledger, Susan
Abstract : Purpose: The purpose of this paper is to explore the perception, readiness and change involved in the implementation of Education 4.0 within the region of Association of Southeast Asian Nations (ASEAN) among policymakers, enablers (lecturers) and receivers (students), within globalisation, referred here as the Fourth Industrial Revolution (4IR). Design/methodology/approach: This study used a mixed method research design using quantitative data from a Likert scale of 1–5, involving: (1) Not Ready; (2) Ready; (3) No Sure; (4) Quite Ready and (5) Extremely Ready. Open-ended questions formed the qualitative approach taken by the researchers to uncover the richness of the respondents' perceptions of Education 4.0. The test items reliability index of 0.744 drew quantitative data from the perspective of the educational policymakers, enablers and receivers to reveal their collective definition of each construct (knowledge, industry and humanity). Findings: This study has exposed the importance of knowing and capturing the interrelated components of an educational ecosystem that exists in higher education (HE) within the ASEAN region. The personal readiness of respondents towards Education 4.0 is very high; yet concern was raised about the financial and managerial readiness of institutions across the region. Originality/value: This study highlighted the dynamic nature of the HE ecosystem and the connectivity between the elements of Education 4.0 – knowledge, industry and humanity within the ASEAN region.